2020
DOI: 10.3390/jcm9092943
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of the Mineralcorticoid Receptor Antagonist Canrenone in COVID-19 Patients

Abstract: Background: In COVID-19 patients, aldosterone via angiotensin-converting enzyme-2 deregulation may be responsible for systemic and pulmonary vasoconstriction, inflammation, and oxidative organ damage. Aim: To verify retrospectively the impact of the mineralcorticoid receptor antagonist canrenone i.v. on the need of invasive ventilatory support and/or all-cause in-hospital mortality. Methods: Sixty-nine consecutive COVID-19 patients, hospitalized for moderate to severe respiratory failure at Fondazione Istituti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 31 publications
(37 reference statements)
1
13
0
1
Order By: Relevance
“…Taken together, these data support a rationale for further testing of mineralocorticoid antagonism to attenuate tissue damage in COVID-19 mediated by endothelial injury, particularly in men. Early randomized clinical trials with a small sample size showed beneficial effects of anti-androgen therapy in mild-to-moderate and severe COVID-19 infection by improving the virus clearance, and reducing time to clinical remission [70][71][72]. Well-powered clinical trials are next needed to investigate a potential beneficial effect of mineralocorticoid antagonism to reduce the risk of COVID-19 adverse outcomes such as organ dysfunction, hospitalization and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, these data support a rationale for further testing of mineralocorticoid antagonism to attenuate tissue damage in COVID-19 mediated by endothelial injury, particularly in men. Early randomized clinical trials with a small sample size showed beneficial effects of anti-androgen therapy in mild-to-moderate and severe COVID-19 infection by improving the virus clearance, and reducing time to clinical remission [70][71][72]. Well-powered clinical trials are next needed to investigate a potential beneficial effect of mineralocorticoid antagonism to reduce the risk of COVID-19 adverse outcomes such as organ dysfunction, hospitalization and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Increased plasma aldosterone levels associated with disease severity in COVID-19 patients ( Villard et al, 2020 ) suggest that MRBs may have beneficial effects in COVID-19. A recent study concluded that canrenone decreased all-cause mortality and improved the clinical outcome in a small cohort of 30 COVID-19 patients with diseases ranging from moderate to severe (M. Vicenzi et al, 2020 ). Another diuretic, furosemide, significantly decreased lipopolysaccharide-induced proinflammatory cytokine production in cell lines and potently inhibited IL-6 and TNF-α release ( Z. Wang, Y. Wang, et al, 2020 ), suggesting its potential use in hypercytokinemic conditions in COVID-19.…”
Section: Cardiovascular Drugs and Ace2mentioning
confidence: 99%
“…Vicenzi et al. ( 32 ) gave canrenone intravenously to COVID-19 patients admitted to hospital with moderate to severe respiratory failure. Canrenone is a metabolite of spironolactone and has the advantage that it can be given intravenously.…”
Section: Introductionmentioning
confidence: 99%